Association of myeloid-derived suppressor cells with hematopoietic recovery after high-dose chemotherapy in multiple myeloma - V. S. Anmut; T. V. Tyrinova; E. V. Batorov; T. A. Aristova; S. A. Sizikova; G. Yu. Ushakova; V. V. Denisova; E. R. Chernykh (Медицинская иммунология)
Myeloid-derived suppressor cells (MDSCs) play an important role in the immune response regulation in many pathologies, primarily in malignant tumors, but their role in the hematopoietic stem cell engraftment and the hematopoietic recovery after high-dose chemotherapy and autologous stem cell transplantation remains practically unexplored. This study is aimed at studying the correlation between the number of MDSC subpopulations and blood parameters at the stage of hematopoietic recovery after high-dose chemotherapy and autologous hematopoietic stem cell transplantation in patients with multiple myeloma (MM). Circulating MDSCs were assessed at the stage of leukopenia recovery (absolute leukocyte count in peripheral blood (PB) > 1 x 109/L) by flow cytometry. The number of transplanted CD34+CD45+ hematopoietic stem cells was 4.38 x 106/kg (IQR (3.1—5.6) x 106/kg). The duration of recovery from leukopenia varied from 8 to 18 days (Me 12 days). The number of MDSCs at the engraftment was not associated with the number of CD34+ cells/kg in the graft. The relative number of monocytic MDSCs (M-MDSCs, CD14+HLA-DRlow/-) directly correlated with the number of monocytes at the stage of recovery from leukopenia (R = 0.417, p = 0.002). Granulocytic MDSCs (PMN-MDSCs, Lin-HLA-DR-CD33+CD66b+) were characterized by an inverse correlation with the number of monocytes (R = -0.493, p = 0.0003) while the association with the absolute number of neutrophils was weak (R = 0.273, p = 0.048). The number of lymphocytes at the stage of recovery from leukopenia had an inverse correlation with PMN-MDSCs (R = -0.347, p = 0.014) and did not correlate with M-MDSCs. When analyzing the duration of leukopenia, an inverse correlation with this indicator was revealed for the percentage and absolute number of M-MDSCs (R = -0.347, p = 0.018 and R = -0.469, p = 0.0008, respectively). Multiple regression analysis showed dependence of the lymphopenia duration on the proportion of circulating M-MDSCs (p = 0.014) and the number of transplanted CD34+ cells/kg (p = 0.032). According to the data of multivariate analysis of variance, the number of transplanted CD34+ cells/kg and the number of M-MDSCs were significant factors for the duration of leukopenia. At the same time, such clinical parameters as the depth of response and minimal residual disease status before high-dose chemotherapy and hematopoietic stem cell transplantation, as well as the MM stage, did not affect the duration of hematopoietic recovery. Thus, the obtained results indicate the association of a higher number of M-MDSCs with a shorter duration of leukopenia after high-dose chemotherapy with autologous stem cell transplantation and indicate a positive role of M-MDSCs in hematopoietic recovery in the early post-transplant period in patients with MM.